PENGARUH PENDAPATAN ASLI DAERAH, BELANJA MODAL, DAN KETIMPANGAN DISTRIBUSI PENDAPATAN TERHADAP IPM DI KABUPATEN/KOTA PROVINSI BALI PERIODE 2013-2020 - Subagia, I Gusti Ngurah Kadek Agus; Utama, Made Suyana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
The purpose of this study was to analyze the District Own Source Revenue, capital expenditures, and Inequality of Income Distribution on the Human Development Index in the Regency/City of Bali Province, either partially or simultaneously. The data used are secondary data, namely PAD data, capital expenditures, Gini ratio coefficient and HDI in the Regency/City of Bali Province for the 2013-2020 period so that the number of observations is 72 observations. The analysis technique used is multiple linear regression analysis with the help of Eviews software. The results of the study show that simultaneously PAD, Capital Expenditures, and Inequality of Income Distribution have an effect on the Human Development Index in the Regency / City of Bali Province. Partially PAD and Capital Expenditure have a positive effect on the Human Development Index. Partially the inequality of income distribution has a negative effect on the Human Development Index. The implication of this research is that the high regional income generation causes PAD to be more widely used to finance capital expenditures which have an impact on equitable development which is directly proportional to the rate of economic growth so that people's welfare can be achieved